Skull and partial skeleton of a new pachycetine genus (Cetacea, Basilosauridae) from the Aridal Formation, Bartonian middle Eocene, of southwestern Morocco - Gingerich, Philip D.; Amane, Ayoub; Zouhri, Samir (PLOS ONE, 2022)
Pachycetus paulsonii, Pachycetus wardii, and Antaecetus aithai are middle Eocene archaeocete whales found in Europe, North America, and Africa, respectively. The three are placed in the new basilosaurid subfamily Pachycetinae. Antaecetus is a new genus known from Egypt and Morocco, and the only pachycetine known from a substantial postcranial skeleton. The skull of A. aithai described here resembles that of Saghacetus osiris in size, but lacks the narrowly constricted rostrum of Saghacetus. Antaecetus is smaller than Pachycetus and its teeth are more gracile. Upper premolars differ in having two rather than three accessory cusps flanking the principal cusp. Pachycetines differ from dorudontines in having elongated posterior thoracic and lumbar vertebrae like those of Basilosaurus, but differ from basilosaurines and from dorudontines in having conspicuously pachyosteosclerotic vertebrae with dense and thickly laminated cortical bone surrounding a cancellous core. Pachycetinae are also distinctive in having transverse processes on lumbar vertebrae nearly as long anteroposteriorly as the corresponding centrum. We infer from their pachyosteosclerotic vertebrae that pachycetines were probably sirenian-like slow swimmers living in shallow coastal seas and feeding on passing fish and mobile invertebrates.